Overview of multiplex immunohistochemistry/immunofluorescence techniques in the era of cancer immunotherapy - Tan, Wei Chang Colin; Nerurkar, Sanjna Nilesh; Cai, Hai Yun; Ng, Harry Ho Man; Wu, Duoduo; Wee, Yu Ting Felicia; Lim, Jeffrey Chun Tatt; Yeong, Joe; Lim, Tony Kiat Hon (Cancer communications (London, England), 2020)
Conventional immunohistochemistry (IHC) is a widely used diagnostic technique in tissue pathology. However, this technique is associated with a number of limitations, including high inter‐observer variability and the capacity to label only one marker per tissue section. This review details various highly multiplexed techniques that have emerged to circumvent these constraints, allowing simultaneous detection of multiple markers on a single tissue section and the comprehensive study of cell composition, cellular functional and cell‐cell interactions. Among these techniques, multiplex Immunohistochemistry/Immunofluorescence (mIHC/IF) has emerged to be particularly promising. mIHC/IF provides high‐throughput multiplex staining and standardized quantitative analysis for highly reproducible, efficient and cost‐effective tissue studies. This technique has immediate potential for translational research and clinical practice, particularly in the era of cancer immunotherapy.